High folate receptor expression in gliomas can be detected in vivo using folate-based positron emission tomography with high tumor-to-brain uptake ratio divulging potential future targeting possibilities - Miner, Maxwell W. G.; Liljenbäck, Heidi; Virta, Jenni; Kärnä, Salli; Viitanen, Riikka; Elo, Petri; Gardberg, Maria; Teuho, Jarmo; Saipa, Piritta; Rajander, Johan; Mansour, Hasan Mansour A; Cleveland, Nathan A.; et al. (Frontiers in Immunology, 2023)
Non-invasive imaging techniques such as positron emission tomography (PET) are extremely important for cancer detection and characterization especially for difficult to biopsy or extremely delicate organs such as the brain. The folate analogue 1,4,7-triazacylononane-1,4,7-triacetic acid-conjugated folate radiolabeled with aluminum fluoride-18 ([18F]FOL) has been previously shown to accumulate preferentially in tumor cells with an overexpression of folate receptors (FRs) and here was investigated for its ability to detect orthotopic gliomas in a rat model. In addition, we studied the expression of FRs in human glioblastoma samples to investigate if an analogous relationship may exist. Nine BDIX rats were injected with BT4C rat glioma cells into the right hemisphere of the brain. Animals were imaged with gadolinium-enhanced magnetic resonance imaging on days prior to PET/computed tomography (CT) imaging. Animals were divided into two groups and were PET/CT imaged with either [18F]FOL or 2-deoxy-2-18F-fluoro-ᴅ-glucose ([18F]FDG) on 19 and 32-days post glioma grafting. Two subjects were also PET/CT imaged with [18F]FOL on day 16. Biodistribution was studied and brains were cryosectioned for autoradiography, immunofluorescence and histological studies. Patient-derived paraffin-embedded glioblastomas were sectioned and stained with similar methods. PET imaging showed an increase of [18F]FOL tumor-to-brain uptake ratio (TBR) over the study duration from day 16/19 (3.3 ± 0.9) increasing to 5.7 ± 1.0 by day 32. [18F]FDG PET-imaged rats had a consistent TBR of 1.6 ± 0.1 throughout the study. Ex vivo autoradiography results revealed an exceptionally high TBR of 116.1 ± 26.9 for [18F]FOL while the [18F]FDG values were significantly lower giving 2.9 ± 0.6 (P<0.0001). Immunostaining demonstrated an increased presence of FR-α in the BT4C gliomas versus the contralateral brain tissue, while FR-β was present only on glioma periphery. Human sections assayed showed similar FRs expression characteristics. This study shows upregulation of FR-α inside glioma regions in both human and animal tissue, providing a biochemical basis for the observed increased [18F]FOL uptake in animal PET images. These results suggest that folate receptor targeting imaging and therapeutic compounds may possess clinically relevant translational abilities for the detection and treatment of gliomas.